Access, adoption, and diffusion: The long-term impacts of improved vegetable and fish technologies in Bangladesh - Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2010)
This series of notes summarizes findings of a project entitled "What development interventions work?" undertaken by researchers of the Chronic Poverty Research Centre, the International Food Policy Research Institute, and Data Analysis and Technical Assistance Ltd. As part of a larger longitudinal study that resurveyed 1,907 households and 102 villages in 14 of Bangladesh's 64 districts, the project focused on assessing the long-term impacts of a number of anti-poverty interventions—specifically, microfinance, agricultural technology, and educational transfers—on a range of monetary and nonmonetary measures of well-being. This note focuses on the long-term impacts on men's and women's assets of disseminating agricultural technologies to individuals compared with groups. It is hoped that these results will help policymakers, donors, and other stakeholders to effectively evaluate different interventions thereby contributing to the design of future anti-poverty programs in South Asia. Among the poverty-alleviation interventions undertaken by government and civil society organizations in Bangladesh are foodbased strategies designed to increase incomes and to alleviate micronutrient deficiencies. Polyculture fish and vegetables technologies are considered to have the potential to improve both poverty and micronutrient status by increasing the supply of micronutrients to household producers and the general population, by improving the incomes of household producers, and by lowering or keeping constant fish and vegetable prices in the face of rising demand due to population and income growth.